Interprovincial Unionization and the Environment - Das, Anupam; Hudson, Ian; Hudson, Mark (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
The relationship between labour movements and the environment has been the subject of considerable debate but little empirical research. Using panel data for Canadian provinces between 2001 and 2019, this article investigates the relationship between unionization rates and two measures of environmental quality: greenhouse gas emissions and total particulate matter pollution. We find that higher unionization rates are associated with lower emissions for both these measures. This finding suggests that stronger labour organizations do not lead to detrimental environmental outcomes.